Line-Up Image Position in Simultaneous and Sequential Line-Ups: The Effects of Age and Viewing Distance on Selection Patterns - Nyman, Thomas J.; Antfolk, Jan; Lampinen, James Michael; Korkman, Julia; Santtila, Pekka (Frontiers in Psychology, 2020)
It is known that children and older adults produce more false alarms in target absent line-ups and that weaker facial encoding increases choosing bias. However, there has been no investigation of how age or facial encoding strength impacts line-up position selections in either sequential or simultaneous line-ups. In the present study, we presented participants with four live targets (one by one) while manipulating sequential and simultaneous line-ups between participants and target present and target absent line-ups within participants. In order to investigate facial encoding strength, we presented the targets at distances between 5-110 meters. Our main hypotheses were that children due to deficits with inhibition would be more biased towards indiscriminate selections in the first position of sequential line-ups compared with subsequent line-up positions, and that first position selections would increase for all age groups as facial encoding became weaker. In simultaneous line-ups, we expected to find a top row bias. In our sample (N = 1588 participants; 6-77), we found that younger children (6-11) and the oldest adults (60-77) showed a first position bias in sequential line-ups, and as facial encoding became weaker, all age groups (12-17, 18-44, 45-59) showed an increased tendency to make first position selections. We also found a weak top row preference in simultaneous line-ups, which was moderated by age and increased distance. The main finding is that the results suggest that younger children and the oldest adults had a tendency towards a first position selection bias in sequential line-ups. Based on the combined results, we recommend caution when using sequential line-ups with younger children or older adults.